Nickel oxide encapsulated nitrogen-rich carbon hollow spheres with multiporosity for high-performance pseudocapacitors having extremely robust cycle life. Issue 1 (29th October 2014) - Kim, Se Yun; Jeong, Hyung Mo; Kwon, Jun Ho; Ock, Il Woo; Suh, Won Hyuk; Stucky, Galen D.; Kang, Jeung Ku
Abstract : Nickel oxide-encapsulated hollow carbon nitride spheres with multiporosity show an ∼250% enhancement in capacitance, in addition to their robust cycle life. Abstract : We report nickel oxide encapsulated nitrogen-rich carbon hollow spheres with multiporosity, where micropores increase the number of active sites to store redox ions and mesopores enhance the ionic diffusivity of encapsulated nickel oxide, which lead to high capacitance and robust cycle life. Moreover, a high-performance full capacitor showing excellent energy and power densities is realized.